Financial Literation and Its Effect on the Performnce and Sustainability of Micro Small and Medium Enterprises in Banyumas - Retno Kurniasih; Siti Zulaikha Wulandari; Tiladela Luhita (Faculty of Economics and Business, Jenderal Soedirman University, 2020)
The purpose of this study was to analyze the effect of financial literacy on the performance and sustainability of MSMEs in the Banyumas Regency. This research is descriptive and quantitative, using the method of regression analysis and using SPSS 16.0 software for Windows. The number of samples in this study was 100 MSMEs in Banyumas Regency. The sampling technique in this study will determine by the nonprobability sampling technique. The results of this study indicate that financial literacy influences the performance and sustainability of MSMEs.